2000
DOI: 10.1128/aem.66.4.1749-1753.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Integrative Element, ICE St1 , in the Lactic Acid Bacterium Streptococcus thermophilus

Abstract: The 35.5-kb ICESt1 element of Streptococcus thermophilus CNRZ368 is bordered by a 27-bp repeat and integrated into the 3 end of a gene encoding a putative fructose-1,6-biphosphate aldolase. This element encodes site-specific integrase and excisionase enzymes related to those of conjugative transposons Tn5276 and Tn5252. The integrase was found to be involved in a site-specific excision of a circular form. ICESt1 also encodes putative conjugative transfer proteins related to those of the conjugative transposon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…THE ICESt1/ICESt3 FAMILY ICESt1 was first described as a 35-kb polymorphic region in the chromosome of the lactic acid bacterium Streptococcus thermophilus CNRZ368 (100). Further investigations revealed that this region contains an ICE integrated in the 3′ end of fda, a gene coding for the 1,6-bisphosphate aldolase (101). fda is also the target for the integration of another closely related ICE named ICESt3, initially identified in S. thermophilus CNRZ385 (102).…”
Section: Replication Of Icebs1mentioning
confidence: 99%
See 1 more Smart Citation
“…THE ICESt1/ICESt3 FAMILY ICESt1 was first described as a 35-kb polymorphic region in the chromosome of the lactic acid bacterium Streptococcus thermophilus CNRZ368 (100). Further investigations revealed that this region contains an ICE integrated in the 3′ end of fda, a gene coding for the 1,6-bisphosphate aldolase (101). fda is also the target for the integration of another closely related ICE named ICESt3, initially identified in S. thermophilus CNRZ385 (102).…”
Section: Replication Of Icebs1mentioning
confidence: 99%
“…They share a common organization in two main regions: a core region that encompasses the genes and sequences necessary for their intra-and intercellular mobility, and a highly variable region delimited by the attL site and the regulation module ( Fig. 6) (70,101,102). The core region of ICESt1 and ICESt3 is subdivided into three modules: the nearly identical conjugation and recombination modules that share 95% identity at the nucleotide level and a more variable regulation module (Fig.…”
Section: Genetic Organizationmentioning
confidence: 99%
“…Interestingly, one of the rare S. thermophilus plasmids (30) showed sequence similarity to the origin of replication of S. thermophilus phages (25). However, in contrast to the situation for E. coli, where phages can replicate as extrachromosomal elements (phage P1), no good evidence for prophage-like plasmids exists for lactic acid bacteria (15). L. lactis phages are therefore under a much greater selection pressure to diversify within the species or to accept "foreign" phage modules from the environment than S. thermophilus phages.…”
mentioning
confidence: 99%
“…They carry sequences almost identical to L. lactis sequences, including insertion sequences (ISs), a restrictionmodification module, and a cadmium resistance module (19,20,54). Two of these elements, ICESt1 and ICESt3, harbor very closely related recombination modules that encode a tyrosine integrase and an excisionase.…”
mentioning
confidence: 99%
“…Two of these elements, ICESt1 and ICESt3, harbor very closely related recombination modules that encode a tyrosine integrase and an excisionase. They excise by site-specific recombination between two 27-bp direct repeats included in their two attachment sites, attL and attR (20,54). A DNAdamaging agent, mitomycin C (MC), derepresses the site-specific excision of ICESt1 and ICESt3 (4).…”
mentioning
confidence: 99%